Overexpression of Cutinase without Mediation of Signal Peptide - Wang, Lei (Cutinase: Preparation and Application, 2021)
This study investigated that T. fusca cutinase without a signal peptide (cutinaseNS) was expressed in E. coli, indicating the majority of the cutinase activity was located in the culture medium. Biochemical characterization of cutinaseNS has similar to those of the wild type. The majority of inactive cutinaseNS was located in the cytoplasm of E. coli. Furthermore, T. fusca cutinase was confirmed to have hydrolysis activity toward phospholipids, an important component of the cell membrane. Compared with cells expressing the inactive cutinaseNS, cells expressing cutinaseNS showed increased membrane permeability and irregular morphology, but no obvious cell lysis was observed in this process. Based on these results, a hypothesis was proposed to explain the underlying mechanism for the extracellular release of cutinaseNS as “cell leakage induced by the limited phospholipid hydrolysis of cutinaseNS”. The increased membrane permeability could also enhance the extracellular expression of recombinant secretory enzymes and make the extracellular expression of recombinant cytosolic enzymes realized. This novel strategy will have significant potential application in the large-scale preparation of cutinase and other industrial proteins.